2012 provisional classification criteria for polymyalgia rheumatica: a European League Against Rheumatism/American College of Rheumatology collaborative initiative. Issue 4 (2nd March 2012) - Dasgupta, Bhaskar; Cimmino, Marco A; Maradit-Kremers, Hilal; Schmidt, Wolfgang A; Schirmer, Michael; Salvarani, Carlo; Bachta, Artur; Dejaco, Christian; Duftner, Christina; Jensen, Hanne Slott; Duhaut, Pierre; Poór, Gyula; et al.
Abstract : The objective of this study was to develop EULAR/ACR classification criteria for polymyalgia rheumatica (PMR). Candidate criteria were evaluated in a 6-month prospective cohort study of 125 patients with new onset PMR and 169 non-PMR comparison subjects with conditions mimicking PMR. A scoring algorithm was developed based on morning stiffness >45 minutes (2 points), hip pain/limited range of motion (1 point), absence of RF and/or ACPA (2 points), and absence of peripheral joint pain (1 point). A score ≥4 had 68% sensitivity and 78% specificity for discriminating all comparison subjects from PMR. The specificity was higher (88%) for discriminating shoulder conditions from PMR and lower (65%) for discriminating RA from PMR. Adding ultrasound, a score ≥5 had increased sensitivity to 66% and specificity to 81%. According to these provisional classification criteria, patients ≥50 years old presenting with bilateral shoulder pain, not better explained by an alternative pathology, can be classified as having PMR in the presence of morning stiffness>45 minutes, elevated CRP and/or ESR and new hip pain. These criteria are not meant for diagnostic purposes.